Improvement Strategy to Ordering Product of Nanggu Footwear - Eryandez, Ryan; Larso, Dwi (The Indonesian Journal of Business Administration, 2015)
Abstract. The emergence of competition in business world is unavoidable. The competition leads the current business to face various opportunities and threats both from the inside and the outside company. Due to the increasing competition, the company must understand what and how to manage its resources. Competitive advantage can be derived from various activities of the company such as designing, producing, marketing, delivering, and supporting its products.In this paper, will analyze how ordering production strategy of Nanggu Footwear and the internal condition of shoes business which run by the Nanggu Footwear. The issue comes from the craftsmen the team hired, Along with the manufacturing process, there are also some issues regarding the manufacturing time required by the craftsmen. Commonly, there are frequent delays in the manufacturing process and the supply of leather material used for footwear is lacking and relatively expensive. There Ã‚Â are needed improvement strategy to ordering product in effort to solve many obstacles that happen in actual condition.Ã‚Â Based on the result of the company activity, the proposed improvement strategy to ordering product includes managing the craftsmen (man), managing supply of raw material, procurement of tools which are needed by craftsmen (machinery), making agreement to craftsmen by contract system in ordering product (method/procedures) and controlling the process of making shoes (measurement).Keyword: improvement strategy to ordering product, shoe making, local brand fashion, footwear, leather shoeÃ‚Â